Answer:
Both questions are true. I believe so anyways..
Explanation:
Correct me if I'm wrong.
- For both equations all you would have to do is multiply.
As for the first equation -3 xy is the equation and sense x = 2 and y= 3,
the equation would now look like this: -3 23. Knowing that, you would multiply all the numbers together to get -18. It turns out negative from -3.
- As for the second equation, you would do the same.
Having x 3y as the equation and x = -2 and y = 3. The equation will look like this: -2 33. Now to multiply to get -24. Again, it turns out negative because x = -2.
Hope this helps in anyway possible.